Developing a Learning Design with Augmented Reality to Improve Critical Thinking and Problem-Solving Skill - Utami, Nisaudzakiah; Setiawan, Agus; Hamidah, Ida (Universitas Ahmad Dahlan, 2025)
This research was conducted to develop and evaluate learning design using Augmented Reality (AR), which aims to improve critical thinking and problem-solving skills in basic turning topics. Methodology – The learning design was developed using Design-Based Research (DBR), with process stages: preliminary study, development, and evaluation. Literature review and instruments inform the learning design of teachers and student needs on basic learning to ensure students have the skills for practice. Part of the learning design, including modules and storyboards, is created to provide an overview of learning design outcomes. The learning design and storyboard are evaluated by learning design experts and mechanical engineering teachers. Findings – The result of the development learning design is feasible because it is needed based on the problem indicator points in the preliminary study activity. So, this learning design will be a reference for AR-based learning media. Significance – These findings indicate that learning is based on Augmented Reality (AR) and teaching that uses the PJBL model, and this must be fostered in machining engineering learning to increase students' success in making work steps for a product. This learning design helps teachers improve teaching and student learning in the classroom before practicing on real machines.